(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
This article examines modern methods of strengthening tax control and combating the shadow economy in the digital economy. The article presents a quantitative analysis of the current state of the shadow economy globally and in the Republic of Uzbekistan, based on World Bank calculations.